Kombinasi Persamaan Rosin-Rammler dan Metode Pengapungan Batang (Buoyancy Weighing-Bar Method) pada Penentuan Distribusi Ukuran Gelembung Air dalam Kerosin - Tambun, Rondang; Sijabat, Gabriella J J; Sidebang, Theresia J; Tambun, Bungaran (Talenta Publisher (Universitas Sumatera Utara), 2023)
Droplet size distribution is one of the important physical parameters in the industry that use emulsions. In this research, a new method namely the Buoyancy Weighing-Bar Method is used to determine the droplet size distribution. In this research, droplet size distribution of kerosene in water is predicted which cannot be determined by the Buoyancy Weighing-Bar Method is carried out by using a combination of the Rosin-Rammler equation and measurement data by the Buoyancy Weighing-Bar Method. From the research results it was found that the combination of the Rosin-Rammler equation and the Buoyancy Weighing-Bar Method can be performed to predict the droplet size distribution of kerosene in water, and the results are comparable to the results obtained with the Coulter counter method. In the use of various types of bars, variations in bars shape and variations in bar length, the combination of the Rosin-Rammler equation and the Buoyancy Weighing-Bar Method can measure the droplet size distribution of kerosene in water.Â